COMPARATIVE STUDY BETWEEN LAPAROSCOPIC VERSUS APPENDECTOMY IN OBESE PATIENTS: A COHORT STUDY. - Ranjan, Anupam; Rani, Sweta; Sumi, Sheto; Ranjan, Shri Krishna (Student's Journal of Health Research Africa, 2024)
Background The two main surgical therapies for appendicitis are laparoscopic appendectomy (LA) and open appendectomy (OA). Appendicitis is a major surgical emergency. The study aimed to evaluate the outcomes of laparoscopic appendectomy versus open appendectomy in obese patients. Methods Ninety patients with appendicitis with a BMI of 30 or more were randomised into two groups: the OA group, which included 45 individuals, and the LA group, which included 45 patients. SPSS Statistics Version 23.0 was used to gather and analyse data on demographics, postoperative complications, length of hospital stay, surgical time, pain levels, and recovery durations. Results The socio-demographic characteristics of the patients were similar across both groups, with an average age of 35.6 ± 10.2 years in the LA group and 36.1 ± 11.3 years in the OA group. In comparison to the OA group, the LA group experienced considerably shorter hospital stays (2.1 ± 0.7 days) and operative times (45.3 ± 10.1 minutes vs. 60.4 ± 12.3 minutes, p < 0.001). The LA group experienced less postoperative complications (11.1% vs. 26.7%, p = 0.04). The LA group also had reduced pain levels 24 hours after surgery (3.5 ± 1.4 vs. 5.6 ± 1.7, p < 0.001). Readmission rates and delayed complications were among the long-term outcomes that did not significantly differ across the groups. Conclusion When compared to OA, LA is linked to shorter operating and recovery periods, less pain during surgery, and fewer problems in obese patients. These results validate LA as the recommended surgical treatment for obesity-related appendicitis. Recommendations Due to its benefits in terms of efficiency and safety, LA ought to be the norm for treating appendicitis in obese patients. It is advised to perform more studies with larger sample sizes and longer follow-up times in order to validate these results and evaluate long-term effects.